Music-Assisted Progressive Muscle Relaxation in Patients with Locally Advanced Gastric Cancer Undergoing Concurrent Chemoradiotherapy - Juwei Zhong; Fengyun Zhao (Noise and Health, 2025)
Objective: This study aimed to explore the effect of music-assisted progressive muscle relaxation on patients with locally advanced gastric cancer (LAGC) undergoing concurrent chemoradiotherapy (CCRT). Methods: A retrospective study was conducted on the medical records of 124 patients with LAGC who received CCRT in Jiaozhou Central Hospital from December 2021 to November 2023. These patients were divided into the conventional care group (n = 65) and the music relaxation group (n = 59) on the basis of different nursing methods. Negative emotions (Hospital Anxiety and Depression Scale [HADS]), sleep quality (Self-Rating Scale of Sleep [SRSS]), and quality of life (Quality-of-Life Questionnaire-Chinese Cancer Chemotherapy Patients) were compared between the two groups before and after treatment. Results: After treatment, the HADS and SRSS scores of the music relaxation group were significantly lower than those of the conventional care group (P < 0.001), and the Quality-of-Life Questionnaire-Chinese Cancer Chemotherapy Patients scores of the music relaxation group were significantly higher than those of the conventional care group (P < 0.001). Conclusion: Music-assisted progressive muscle relaxation can improve the psychological state of patients with LAGC undergoing concurrent radiotherapy, promote sleep quality and help improve quality of life.